Development zones and firms' performance: the impact of development zones on firms' performance for a Chinese industrial cluster. Issue 5 (4th May 2023) - Liu, Ye; Wu, Yiyun; Zhu, Xiwei
ABSTRACT: This paper examines the policy effect of development zones on firms' performance, excluding the agglomeration effect. We constructed an industrial cluster dataset on China's manufacturing industries to identify the impacts on firms' productivity and other performance indices after the establishment of development zones in 2006. Based on the estimated results obtained from a difference-in-differences analysis, development zones are conducive to promoting firms' performance, and the policy effect is heterogeneous across industrial clusters, regions and firms. The findings drawn from this study can be beneficial to policymakers in their pursuit of promoting regional development through favourable industrial policies.